Behavior and Mechanics of Multifunctional Materials and Composites XII 2018
DOI: 10.1117/12.2291921
|View full text |Cite
|
Sign up to set email alerts
|

Current and future needs and research for composite materials NDE

Abstract: The use of composite materials continues to increase in the aerospace community due to the potential benefits of reduced weight, increased strength, and manufacturability. The ability to characterize damage in carbon fiber reinforced polymer composite components is required to facilitate damage progression models capable of yielding accurate remaining life predictions. As these composite structures become larger and more complex, nondestructive evaluation (NDE) techniques capable of quantifying and fully chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This is crucial for successful damage progression models, which are responsible for remaining life predictions of the structure. For example, it has been reported that the depth of delamination is directly related to the damage progression mechanisms (Canturri et al 2013;Elliott Cramer 2018), so it has to be fully defined by the monitoring system. Different manufacturing processes and novel materials will require different characterization data and assessment of all defects that are present in the structure.…”
Section: Discussionmentioning
confidence: 99%
“…This is crucial for successful damage progression models, which are responsible for remaining life predictions of the structure. For example, it has been reported that the depth of delamination is directly related to the damage progression mechanisms (Canturri et al 2013;Elliott Cramer 2018), so it has to be fully defined by the monitoring system. Different manufacturing processes and novel materials will require different characterization data and assessment of all defects that are present in the structure.…”
Section: Discussionmentioning
confidence: 99%
“…Another significant challenge is the automated fiber placement technique, which involves the robotic layering of pre-impregnated fibers on a composite panel. This method can introduce defects such as gaps, laps, and twists [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the longevity of modern aerospace structures depends on variable environmental conditions, making it difficult to accurately predict the end-of-life of a component based on flight hours alone. To prevent catastrophic failures and unnecessary and costly component replacements, critical components are inspected regularly using non-destructive evaluation (NDE) methods [3,4].…”
Section: Introductionmentioning
confidence: 99%